STILISTIKA DALAM NOVEL AYAH KARYA ANDREA HIRATA - Laili Fatmalinda; Wahyudi Siswanto; Endah Tri Priyatni (Graduate School of Universitas Negeri Malang, 2016)
This research aims to to describe the peculiarities stilistika form of diction , sentence structure, and the father figure of speech in the novel by Andrea Hirata . This study used a qualitative approach to the type of content analysis study (Content Analysis). Based on the analysis, it was found the uniqueness of diction, sentence structure, figure of speech in the novel by Andrea Hirata 's father. The data found in this study as many as 59 data.Penelitian ini bertujuan mendeskripsikan stilistika berupa kekhasan diksi, struktur kalimat, dan majas dalam novel ayah karya Andrea Hirata. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian analisis isi (Content Analysis). Berdasarkan hasil analisis, ditemukan adanya kekhasan diksi, struktur kalimat, majas dalam novel ayah karya Andrea Hirata. Data yang ditemukan dalam penelitian ini sebanyak 59 data.